Image anonymization using clustering with pixelization - Elin Thomas, Ria.; K. Banu, Sharmila; K. Tripathy, B (International Journal of Engineering and Technology, 2018)
With the increasing usage of images to express opinions, feelings and one’s self, on social media, and other websites, privacy concerns become an issue. The need to anonymize a person’s face, or other aspects presented in an image for legal or personal reasons has sometimes been overlooked. Pixelization is a common technique that is used for anonymizing images. However, this technique has been proved to be a not-so-reliable technique, as the images can be restored using de-pixelization techniques. Clustering is usually used in relation to images, for image segmentation. When used in combination with pixelization, it proves to be an effective way to anonymize images. In this paper, the authors investigate the cons of using only pixelization, and prove how the use of clustering can improve the chances of anonymizing effec-tively.
Keywords: Fuzzy C-Means Clustering; Image Anonymization; Pixelization; Privacy.